Physiological and pathological implications of laminins: From the gene to the protein (2007)
The extracellular matrix plays an important role in modulating the behavior of cells with which it interacts. There are a number of families of extracellular matrix (ECM) proteins including collagens, proteoglycans and laminins (LM). LM are the major component of the basal lamina (BL). Here, we review the current knowledge on their structure, self-assembly, binding mechanisms, diverse tissue-expression patterns and its impact on pathology. Studies and hypothesis exploring the role of LM and their polymorphic genes on autoimmune diseases (AIDs) such as systemic lupus erythematosus and Sjögren’s syndrome (SS) are also discussed. © 2018, Taylor and Francis Ltd. All rights reserved.